A National Survey on the Professional Role Conceptions of Journalists in Kenya. (14th September 2017) - Ireri, Kioko
Abstract : The professional role conceptions of journalists have for many years remained a central strand in journalism studies. The present research investigates the professional role conceptions that Kenyan journalists perceive to be the most important in their work. Similarly, the professional role they consider the most important is further analyzed in relation to demographics (age, gender, education, contract type, media type, and media ownership). Findings from a national survey of 504 Kenyan journalists indicate that "providing citizens with information" is the most important role (61.3 percent), followed by "advocate for social change" (51.7 percent). The other major roles include to "support official policies" (46.9 percent), "motivate people to participate in civic activities" (45.6 percent), and "act as watchdog of government" (35.3 percent). The most important role—providing citizens with information—is backed across all demographics with a strong mean of 4.4 on a five-point scale ranging from 1 ("not important at all") to 5 ("extremely important"). However, the difference of means across all the analyzed demographics are not statistically significant.